Extracorporeal membrane oxygenation in 61 neonates: Single‐center experience. Issue 4 (21st December 2016) - Hirakawa, Eiji; Ibara, Satoshi; Tokuhisa, Takuya; Maede, Yoshinobu; Kuwahara, Takako; Ishihara, Chie; Noguchi, Hiroyuki; Naitou, Yoshiki; Yamamoto, Masakatsu; Kibe, Masaya; Yamamoto, Tsuyoshi; Kurimoto, Tomonori; et al.
Abstract: Background: There have been few reports on the outcome of extracorporeal membrane oxygenation (ECMO) in newborn Japanese infants. Methods: A review was carried out of 61 neonates with ECMO between January 1995 and December 2015 at a single center. ECMO was used in neonates with oxygenation index >20 after conventional treatment. Background factors, such as etiology, vascular access mode (veno‐venous [VV] or veno‐arterial [VA]), number of days with ECMO, and early ECMO (within 24 h after birth), were analyzed in relation to outcome with respect to survival to hospital discharge (SHD). Results: Survival to hospital discharge was achieved in 35 infants (57%), while the remaining 26 died during hospital stay. Gestational age at birth was significantly higher and number of days with ECMO was significantly lower in SHD infants compared with those with adverse outcome (median, 4.0 vs 5.5 days, respectively; P = 0.008). The SHD rate was significantly higher for those with VV than VA vascular access mode (78%, 18/23 vs 45%, 17/38, respectively; P = 0.016), and for those with than without early ECMO (72%, 28/39 vs 32%, 7/22, respectively; P = 0.003). The SHD rate was relatively high in neonates with meconium aspiration syndrome (86%, 12/14), persistent pulmonary hypertension associated with hypoxic ischemic encephalopathy (75%, 6/8), and emphysema (80%, 4/5). On stepwise logistic regression analysis two independent factors of SHD were identified: early ECMO (OR, 9.63; 95%CI: 2.47–37.6) and ECMO length <8 days (OR, 8.05; 95%CI: 1.94–33.5). Conclusions: Neonates with early ECMO and those with ECMO duration <8 days may benefit from ECMO with respect to SHD.